2021
DOI: 10.1002/aoc.6276
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐assisted preparation of n‐TiO2‐P25/Ag: An efficient and robust photocatalyst for enhancing visible‐light photo‐oxidation of benzyl alcohol

Abstract: This paper describes the novel method of Ag deposition on the surface of TiO 2 , additionally investigates the photocatalytic properties of the new photocatalyst in the oxidation of benzyl alcohol under visible-light as well as sunlight. Silver nanoparticles were deposited on surface of titanium dioxide through the Tollens test method. Ag(0) has been prepared in situ by reduction of [Ag (NH 3 ) 2 ] + by glucose as a moderate and green reducing agent for the first time. The properties of n-TiO 2 -P25/Ag were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…As shown in Table 2, Most of the previous reports were either lacking in selectivity or the conversion ratio [59,60] . Although some studies have shown that increasing catalyst dosage or prolonging reaction time can achieve high conversion, it undoubtedly increases the reaction cost [33,61–63] . This work can achieve a better reaction effect with less catalyst usage and shorter reaction time, which suggests that the reaction system using 15 wt %PI‐TiO 2 as a catalyst has better catalytic performance.…”
Section: Resultsmentioning
confidence: 97%
“…As shown in Table 2, Most of the previous reports were either lacking in selectivity or the conversion ratio [59,60] . Although some studies have shown that increasing catalyst dosage or prolonging reaction time can achieve high conversion, it undoubtedly increases the reaction cost [33,61–63] . This work can achieve a better reaction effect with less catalyst usage and shorter reaction time, which suggests that the reaction system using 15 wt %PI‐TiO 2 as a catalyst has better catalytic performance.…”
Section: Resultsmentioning
confidence: 97%
“…For further comparison, this paper summarizes recent studies on photocatalytic benzyl alcohol oxidation over TiO 2 type catalysts under visible light irradiation, and these results are summarized in Table 2, which suggests that the prepared 150-TiO 2 exhibits excellent performance for the photocatalytic oxidation of benzyl alcohol into benzaldehyde, with high selectivity and conversion ratio under moderate reaction conditions. For example, noble metal loaded (AuNS@TiO 2 , n-TiO 2 -P25/Ag) 40,45 catalysis is not as efficient as 150-TiO 2 , but the catalyst fabrication cost is much higher than that of 150-TiO 2 , and non-metal element N-doped catalysts (T-400, TiO 2 @COF-3) 42,44 can achieve the results of this work only by increasing the amount of the catalyst or increasing the reaction time.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 92%